CD4+/CD8+ ratio positively correlates with coronary plaque instability in unstable angina pectoris patients but fails to predict major adverse cardiovascular events - Dayang Chai; Xiangquan Kong; Shu Lu; Junjie Zhang (SAGE Publishing, 2020)
Background: The association between CD4+/CD8+ ratio and coronary plaque instability in patients with unstable angina pectoris (UAP) has not been investigated. We sought to elucidate the correlation between CD4+/CD8+ ratio and plaque instability in this patient population. Methods: We enrolled 266 UAP patients who underwent pre-intervention optical coherence tomography (OCT) examination and percutaneous coronary intervention in our center from January 2016 to January 2018. Features of coronary plaques in the culprit arteries were classified as unstable plaque and stable plaque. Primary endpoint was occurrence of a major adverse cardiovascular event (MACE). Receiver operating characteristic (ROC) analyses were used to determine the predictive efficacy of the CD4+/CD8+ ratio for a group of unstable plaque patients, and binary logistic regression analysis was performed to evaluate potential independent predictors of plaque instability. All-cause mortality and MACE between the two groups were analyzed. Results: UAP patients with unstable plaque had a higher CD4/CD8 ratio compared with stable plaque patients ( p  < 0.05). Results of binary logistic regression analyses showed that CD4+/CD8+ ratio ⩾1.725 and prior stroke were predictors and risk factors of plaque instability ( p  < 0.05). ROC analyses showed that CD4+/CD8+ ratio ⩾1.725 was predictive of plaque instability in UAP patients. However, the Kaplan-Meier estimate for MACE and all-cause mortality showed no statistical significance. Conclusions: Higher CD4+/CD8+ ratio is associated with higher risk of plaque instability in our cohort of UAP patients. However, CD4+/CD8+ ratio was not an independent predictor of 1-year MACE or all-cause mortality.